Flammability and Mechanical Properties of Ramie Reinforced Poly(lactic Acid) Composites by Using DOPO - Tao, Yu; Yan, Li; Yonglong, Wang (Taylor's University, 2014)
Ramie reinforced poly(lactic acid)(PLA) composites have been receiving a lot of research attention due to their excellent biodegradability. However, poor flammability of the composites limits their application in a few areas such as automobile and aircraft interior. In the present study, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as flame retardant was incorporated into the ramie fibre reinforced composites to render the environment friendly character of the biocomposites in flame-retarded composition. Flame retardancy of the composites was greatly improved according to the UL94 vertical test and limiting oxygen index (LOI) measurements. The composites could achieve a UL94 V-0 rating and LOI value increases from 21.6 for ramie/PLA to 27.5 for the flame-retarded ramie/PLA. Enhanced char yield at higher temperatures was observed according to the thermogravimetric analysis (TGA) results. The influence of DOPO on the mechanical properties of the composites was also studied. DOPO can influence the mechanical properties of the composites. Observation can be made directly from scanning electron microscope (SEM) image that the compatibility between PLA and ramie fibre is disturbed by DOPO introduced into the composites. Not a lot of research has been done on the flame retardancy of natural fibre reinforced PLA composites. Therefore, this study offers benefits for future research on composites flame retarding.